Analysis Of Public Wireless Network Security Using VPN (Case Study At SMK IT Insan Kreatif) - Rizky Akbar Ramadan; Baginda Harahap (Jurnal Serumpun Teknik Informatika, 2025)
This study was conducted to analyze the extent to which the use of a Virtual Private Network (VPN) can improve network security at SMK IT Insan Kreatif Tj.Morawa. The research method used was an experimental quantitative method with descriptive analysis. Data collection was carried out through direct experiments using the Wireshark application to capture network data packets in two scenarios, namely before and after the implementation of VPN. The sniffing data was analyzed to determine the type of protocol used and whether the data was encrypted or still clearly readable. The results showed that before using a VPN, important data such as login credentials on HTTP and FTP protocols could be read in plaintext, while DNS queries were also openly accessible. After using a VPN, all data was encrypted using the TLS/SSL protocol so that sensitive information was no longer visible in the Wireshark capture results. A comparison of the results of three tests showed that VPNs consistently provided better protection against data leaks